Poland as a case study for some aspects of religion, mediatisation, and secularisation - Stachowska, Ewa (Człowiek i Społeczeństwo, 2016)
The interactions between religion and the media are characterized by a great complexity, manifesting itself inter alia in the impact on the spheres of culture, education and religion, making these dimensions almost obliged to subordinate themselves to the influence of the media, as well as to use the media tools in their activity to fulfill the basic or constitutive aims. In this article one of the aspects of the relationship existing between religion and the media will be discussed, namely, the use of the Internet by the Catholic Church – mainly in Poland, though not only – to distribute religious content and ideas, originally contributing to the support of the pastoral ministry and evangelization. At the same time, the features of the recipients of these activities will be outlined, indicating – at least indirectly – the effectiveness and accuracy of both the inevitable and essential alliance between the sacrum and the media nowadays.